Mitochondrial haplotypebased identification of ethanolpreserved rootknot nematodes from Africa - Pagan, C.; Coyne, Danny L.; Carneiro, R.; Kariuki, G.; Luambana, N.; Affokpon, A.; Williamson, V.M. (Scientific Societies, 2015)
The asexual root-knot nematodes (RKNs) (Meloidogyne spp.) exemplified by Meloidogyne incognita are widespread and damaging pests in tropical and subtropical regions worldwide. Comparison of amplification products of two adjacent polymorphic regions of the mitochondrial genome using DNA extracts of characterized RKN strains, including 15 different species, indicate that several species are derived from the same or closely related female lineages. Nevertheless, M. javanica, M. enterolobii, M. incognita, and other key species could each be assigned unique mitochondrial haplotypes based on polymerase chain reaction fragment size and restriction cleavage patterns. M. arenaria isolates did not group as a single haplotype, consistent with other reports of diversity within this species. To test the utility of this assay, we characterized ethanol-preserved samples from 103 single-species isolates from four countries in sub-Saharan Africa (Benin, Nigeria, Kenya, and Tanzania). Mitochondrial haplotypes corresponding to M. javanica and M. incognita were the most prevalent. Samples from western Africa included several instances of M. enterolobii but this species was not detected in samples from East Africa. This protocol provides progress toward a standardized strategy for identification of RKN species from small, preserved samples and a rational starting point for classifying species present in regions where previous knowledge has been limited.The asexual root-knot nematodes (RKNs) (Meloidogyne spp.) exemplified by Meloidogyne incognita are widespread and damaging pests in tropical and subtropical regions worldwide. Comparison of amplification products of two adjacent polymorphic regions of the mitochondrial genome using DNA extracts of characterized RKN strains, including 15 different species, indicate that several species are derived from the same or closely related female lineages. Nevertheless, M. javanica, M. enterolobii, M. incognita, and other key species could each be assigned unique mitochondrial haplotypes based on polymerase chain reaction fragment size and restriction cleavage patterns. M. arenaria isolates did not group as a single haplotype, consistent with other reports of diversity within this species. To test the utility of this assay, we characterized ethanol-preserved samples from 103 single-species isolates from four countries in sub-Saharan Africa (Benin, Nigeria, Kenya, and Tanzania). Mitochondrial haplotypes corresponding to M. javanica and M. incognita were the most prevalent. Samples from western Africa included several instances of M. enterolobii but this species was not detected in samples from East Africa. This protocol provides progress toward a standardized strategy for identification of RKN species from small, preserved samples and a rational starting point for classifying species present in regions where previous knowledge has been limited.The asexual root-knot nematodes (RKNs) (Meloidogyne spp.) exemplified by Meloidogyne incognita are widespread and damaging pests in tropical and subtropical regions worldwide. Comparison of amplification products of two adjacent polymorphic regions of the mitochondrial genome using DNA extracts of characterized RKN strains, including 15 different species, indicate that several species are derived from the same or closely related female lineages. Nevertheless, M. javanica, M. enterolobii, M. incognita, and other key species could each be assigned unique mitochondrial haplotypes based on polymerase chain reaction fragment size and restriction cleavage patterns. M. arenaria isolates did not group as a single haplotype, consistent with other reports of diversity within this species. To test the utility of this assay, we characterized ethanol-preserved samples from 103 single-species isolates from four countries in sub-Saharan Africa (Benin, Nigeria, Kenya, and Tanzania). Mitochondrial haplotypes corresponding to M. javanica and M. incognita were the most prevalent. Samples from western Africa included several instances of M. enterolobii but this species was not detected in samples from East Africa. This protocol provides progress toward a standardized strategy for identification of RKN species from small, preserved samples and a rational starting point for classifying species present in regions where previous knowledge has been limited.The asexual root-knot nematodes (RKNs) (Meloidogyne spp.) exemplified by Meloidogyne incognita are widespread and damaging pests in tropical and subtropical regions worldwide. Comparison of amplification products of two adjacent polymorphic regions of the mitochondrial genome using DNA extracts of characterized RKN strains, including 15 different species, indicate that several species are derived from the same or closely related female lineages. Nevertheless, M. javanica, M. enterolobii, M. incognita, and other key species could each be assigned unique mitochondrial haplotypes based on polymerase chain reaction fragment size and restriction cleavage patterns. M. arenaria isolates did not group as a single haplotype, consistent with other reports of diversity within this species. To test the utility of this assay, we characterized ethanol-preserved samples from 103 single-species isolates from four countries in sub-Saharan Africa (Benin, Nigeria, Kenya, and Tanzania). Mitochondrial haplotypes corresponding to M. javanica and M. incognita were the most prevalent. Samples from western Africa included several instances of M. enterolobii but this species was not detected in samples from East Africa. This protocol provides progress toward a standardized strategy for identification of RKN species from small, preserved samples and a rational starting point for classifying species present in regions where previous knowledge has been limited.